Changes in prolactin receptor location in prostate tumors - López Fontana, Gastón (2021)
Introduction: Prolactin (PRL) binds its receptor (PRLR) and stimulates cell proliferation, differentiation and survival in prostate cancer (PCa) cell lines via STAT5a, MAPK and AKT. Objective: To evaluate the expression of PRL and PRLR in normal and tumor prostate tissues with different Gleason patterns. Methods: Samples of normal, benign prostatic hyperplasia and PCa with different Gleason patterns were selected from radical prostatectomy. The intensity, location and percentage of stained cells for PRL and PRLR were evaluated by Immunohistochemistry. Co-localization was observed by confocal microscopy. Results: PRL was expressed diffusely and with a mild intensity in the cytoplasm of normal and tumor prostate luminal cells. Its expression only augmented in the Gleason 3 pattern (p 0.0001). The immunostaining intensity and the percentage of positive cells for PRLR did not vary between normal and tumor tissues. However, the location of the PRLR was modified by the tumorigenic process. In non-tumor tissues, PRLR expression was mostly in plasma membrane in the apical zone of epithelial cells. In tumor tissues, it was expressed in intracellular vesicles. The co-localization of PRL and PRLR was demonstrated in normal and tumor tissues suggesting that PRL could be acting in an autocrine and paracrine manner. Conclusion: PRL and its receptor were present in the cytoplasm of the epithelial cells of the normal and tumor prostate gland. In tumor tissues, the change in the location and appearance of cryptic PRLRs that store PRL may keep active the different signaling pathways related to cell proliferation and survival.